Metal-organic frameworks/metal nanoparticles as smart nanosensing interfaces for electrochemical sensors applications: a mini-review - Jiang, Min; Liao, Jing; Liu, Chenghao; Liu, Jun; Chen, Peixian; Zhou, Jia; Du, Zhizhi; Liu, Yan; Luo, Yan; Liu, Yangbin; Chen, Fei; Fang, Xiaojun; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Metal-organic frameworks (MOFs) are porous materials with huge specific surface area and abundant active sites, which are composed of metal ions or clusters and organic ligands in the form of coordination bonds. In recent years, MOFs have been successfully applied in many fields due to their excellent physical, chemical, and biological properties. Electrochemical sensors have advantages such as economy, portability, and sensitivity, making them increasingly valued in the field of sensors. Many studies have shown that the electrode materials will affect the performance of electrochemical sensors. Therefore, the research on electrode materials is still one of the hotspots.MOFs are also commonly used to construct electrochemical sensors. However, electrochemical sensors prepared from single MOFs have shortcomings such as insufficient conductivity, low sensitivity, and poor electrochemical catalytic ability. In order to compensate for these defects, a new type of nanocomposite material with very ideal conductivity was formed by adding metal nanoparticles (MNPs) to MOFs. The combination of the two is expected to be widely applied in the field of sensors. This review summarizes the applications of various MNPs/MOFs composites in the field of electrochemical sensors and provides some references for the development of MNPs/MOFs composites-based electrochemical sensors in the future.